A systematic review and meta-analysis on the association between orthostatic hypotension and mild cognitive impairment and dementia in Parkinson's disease - Loureiro, Débora (2023)
Fil: Loureiro, Débora. Universidad de Buenos Aires. Facultad de Ciencias Médicas. Departamento de Fisiología; Argentina